Insights into Kinases of ESKAPE Pathogens for Therapeutic Interventions - Mody, Deepansh; Joshi, Priyanka; Antil, Monika; Gupta, Rakesh K.; Gupta, Vibha (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2024)
Multidrug-resistant ESKAPE pathogens are the leading cause of hospital-acquired infections across the globe, posing challenges for clinicians. Random genetic mutations and constant exposure to antibiotics in healthcare settings result in strains resistant to commonly used antibiotics, creating life-threatening conditions. If the magic of “antibiotics” is to be sustained, a new class of antimicrobials against novel targets is urgently needed. This necessitates understanding and identifying novel biochemical pathways and bacterial virulence factors that can be targeted for therapeutic interventions. Keeping in view the unambiguous role of the kinome in bacterial survival and virulence, this review provides a survey of effector bacterial kinases involved in evading host immune responses and drug resistance. The formation of biofilms is a critical feature associated with the pathogenesis and survival of ESKAPE organisms in the hostile host milieu. Hence, kinases involved in the biofilm pathway are also elucidated for clinical relevance. In addition, endeavors in the development of therapeutics against ESKAPE kinases are also summarized to provide direction to researchers pursuing the field.
Keywords: Kinases